Hematologic disturbs in Down Syndrome: an scoping review protocol (Research, Society and Development, 2026)
Introduction: Down syndrome (DS) is the most common chromosomal disorder and is associated with a broad and distinctive spectrum of hematological abnormalities throughout life, ranging from transient neonatal conditions to persistent disorders and an increased risk of hematological malignancies. Despite extensive scientific production, the available evidence is fragmented across different fields, hindering an integrated understanding of hematological manifestations in DS. Objective: To map and synthesize the available evidence on hematological abnormalities described in individuals with Down syndrome across all age groups, study designs, and healthcare settings. Methods: This scoping review will be conducted in accordance with the Joanna Briggs Institute (JBI) methodology and reported following the PRISMA-ScR guidelines. The research question will be structured using the PCC framework, considering individuals with DS, hematological alterations (erythroid, myeloid, leukocytic, platelet, immunological, bone marrow, and hematological neoplasms), and clinical, epidemiological, experimental, or genetic studies. Searches will be performed in PubMed/MEDLINE, Embase, Scopus, Web of Science, SciELO, the Cochrane Library, and LILACS, with no restrictions on publication date or language. Study selection and data extraction will be carried out independently by two reviewers, and results will be synthesized using a descriptive and narrative approach. Conclusions: This scoping review aims to provide a comprehensive overview of hematological abnormalities in Down syndrome, identify knowledge gaps, and support clinical practice, research development, and future diagnostic and therapeutic strategies.